The Moderating Impact of Firm Size and Environmental Conditions on Entrepreneurial Approaches: A Qualitative Review of Entrepreneurial Orientation, Market Orientation, and Entrepreneurial Marketing. - Ruslaini Ruslaini; Yessica Amelia (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This qualitative literature review examines the moderating effects of firm size and environmental conditions on entrepreneurial orientation (EO), market orientation (MO), and entrepreneurial marketing (EM). The findings reveal that firm size influences the implementation and outcomes of EO, MO, and EM, with smaller firms leveraging flexibility and larger firms utilizing resource scale. Environmental conditions further shape the efficacy of these approaches, with dynamic markets amplifying their impact. The interplay between EO, MO, and EM is emphasized, highlighting their collective role in enhancing adaptability and competitiveness. However, contextual variability and methodological constraints limit the generalizability of the findings. This review contributes to entrepreneurial strategy literature and provides actionable insights for managers to align strategies with organizational characteristics and environmental dynamics. Future research should explore additional moderators and incorporate empirical validation for a more comprehensive understanding.